2018
DOI: 10.1186/s40557-018-0274-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between job stress and functional dyspepsia in display manufacturing sector workers: a cross-sectional study

Abstract: BackgroundJob stress has been reported as a risk factor of psychological changes, which have been shown to be related to gastrointestinal diseases and symptoms such as functional dyspepsia. However, few studies have assessed the relationship between job stress and functional dyspepsia. Therefore, we investigated the relationship between job stress and functional dyspepsia in South Korea.MethodsThis study was conducted between May 23 and July 6, 2016 and included 901 workers in the display manufacturing sector.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
1
11
1
4
Order By: Relevance
“…Men have better response to stress and coping than women and Baruch reported women are more prone to stressors than men (Baruch et al, 2003). Women experience higher levels of occupational stress than men (Shukla & Srivastava, 2016;Nam et al, 2018;Hipp et al, 2015). Women have 40% higher stress than men (American Psychological Association (APA), 2010).…”
Section: Gender and Stressmentioning
confidence: 99%
“…Men have better response to stress and coping than women and Baruch reported women are more prone to stressors than men (Baruch et al, 2003). Women experience higher levels of occupational stress than men (Shukla & Srivastava, 2016;Nam et al, 2018;Hipp et al, 2015). Women have 40% higher stress than men (American Psychological Association (APA), 2010).…”
Section: Gender and Stressmentioning
confidence: 99%
“…High stress levels were found to affect KMHC use in patients with FD. Higher levels of perceived stress increase the risk of dyspepsia [ 36 , 37 ]. Additionally, stress is associated with more clinic visits and health care use [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had linked gastrointestinal alternations with occupational stress or burnout. [22][23][24] This so-called The Great Workfrom-Home Experiment of 2020 can provide insights on the experiences of working from home for those with IBS. According to a study conducted in Singapore, Singaporeans reported some improvements in sleep and exercise, and falling ill less during the lockdown that began in April compared with January when COVID-19 was not prevalent locally.…”
Section: Discussionmentioning
confidence: 99%